Erratum: ZONG-WEI ZHU, XIN-GUI LE, LU-FEI LI, SHI-PIN CHEN & BIN CHEN (2023) Sedum yangjifengensis (Crassulaceae), a new species from Jiangxi, China. Phytotaxa 607 (1): 105–113 - Zhu, Zong-Wei; Le, Xin-Gui; Li, Lu-Fei; Chen, Shi-Pin; Chen, Bin (Phytotaxa, 2023)
N/A